Legal system in the context of Algeria’s accession to the World Trade Organization - Khouatra, Samia (Journal of Human Sciences, 2020)
Algeria is one of countries still negotiating for accession to the World Trade Organization (WTO), greater political will and a better macro-economic framework are now present to promote the accession of Algeria to the largest international organization that organizes the rules governing trade in the world. To join, Algeria must offer an entry ticket for tariff consolidations and services and adopt intellectual property protection rules; all this is to integrate the national economy into the global economic and trade system.